Draft Genome Sequence of a Phytopathogenic Ganoderma sp. Strain That Causes Basal Stem Rot Disease on Oil Palm in Sabah, Malaysia - Christopher Voo Lok Yung; Daniel E. T. Yeo; Chong, Khim Phin; Kenneth F. Rodrigues (2020)
Basal stem rot (BSR) disease on Elaeis guineens is known to be caused by members of the pathogenic fungal genus Ganoderma, especially the species Ganoderma boninense. This species affects oil palm plantation in Sabah, Malaysia. The genome sequence (52.28 Mbp) will add to the representation of this genus, especially in regard to BSR disease.